2023
DOI: 10.1097/yco.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the coronavirus disease 2019 pandemic in schizophrenia: a review

Abstract: Purpose of reviewMultiple countries have reported increased COVID-19 mortality in patients with schizophrenia. The purpose of this review was to synthetize the consequences of the pandemic on patients with schizophrenia including vaccination data.Recent findingsWe have synthetized data on the increased risk of infection and increased mortality, the impact of the pandemic and lockdowns on psychiatric care, vaccination policies, unwillingness to vaccine in patients and the rates of vaccination.SummarySchizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…As the use of antipsychotics in minors is only licensed in Austria for the treatment of bipolar disorder, schizophrenia, or major impulsive aggressive behavior, these rising rates, particularly among females, are highly interesting. Despite research demonstrating a particularly severe impact of the COVID-19 pandemic on people with schizophrenia [ 16 ], few studies have explored a potential increase in first episodes of schizophrenia. One study, conducted in Australia, reported an increase in first-episode admissions for schizophrenia among young people following the introduction of lockdown measures [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the use of antipsychotics in minors is only licensed in Austria for the treatment of bipolar disorder, schizophrenia, or major impulsive aggressive behavior, these rising rates, particularly among females, are highly interesting. Despite research demonstrating a particularly severe impact of the COVID-19 pandemic on people with schizophrenia [ 16 ], few studies have explored a potential increase in first episodes of schizophrenia. One study, conducted in Australia, reported an increase in first-episode admissions for schizophrenia among young people following the introduction of lockdown measures [ 26 ].…”
Section: Discussionmentioning
confidence: 99%